IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA PEMBELAJARAN IPAS DI SD ISLAM AL-AZHAR 43 GORONTALO - Mailangkay, Siti Nurhaliza; Mujahid Damopolii; Alfian Erwinsyah (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2025)
This research aims to determine the process and obstacles in implementing differentiated learning in science and science learning at Al-Azhar 43 Gorontalo Islamic Elementary School. This type of research is qualitative phenomenology, which is the type of approach chosen in this research. This research uses interview, observation and documentation guidelines. The data analysis technique used in this research consists of three stages, namely data reduction, data presentation, and drawing conclusions. The results of the research found things, namely that differentiated learning in science and science learning has been carried out in essence, both from planning, implementation and evaluation. Researchers can draw conclusions from this research that differentiated learning in science and science learning starts from the planning stage by mapping student learning needs through diagnostic assessments which are used as a basis for teachers to design learning which is outlined in the form of teaching modules. Furthermore, teachers' implementation strategies include differentiation of content, processes, products and learning environments. Differentiation here does not mean that teachers differentiate the overall learning per each student, but differentiation here means that teachers are able to create learning plans that accommodate students' learning needs and students feel comfortable in learning.